Geographical indication as a strategic brand resource in the wine sector in Rio Grande do Sul/Brazil - Castro, Virginia Aparecida; Lourenção, Marina Toledo de Arruda; Giraldi, Janaina de Moura Engracia (Revista de Administração da UFSM, 2021)
Purpose: Geographical indications (GIs) are considered a type of brand that is shared by companies in the same sector in order to highlight the origin of a product and have its quality recognized. They have been widely used in the wine sector. This study aims to verify whether geographical indications can be considered an internal resource that generates competitive advantage for the Brazilian wine sector. Furthermore, it also aims to: i) understand the purpose of creating a geographical indication; ii) understand the process of creating the geographical indication and the procedure for authorizing its use; iii) understand what are the unique intangible results obtained by a geographical indication; iv) check the vision of the future concerning the geographical indication. Design/methodology/approach: It was conducted in-depth interviews with government agencies, associations, and winegrowers in Rio Grande do Sul/Brazil. Findings: Therefore, GI projects can be resources that are difficult to copy or replace, building knowledge, identifying terroirs, and redefining production practices. Originality/value: It can lead to the achievement of sustainable competitive advantage with increased exports and differentiated products in the market.